Research on the Effect of Needle Eccentricity on the Jet Flow Characteristics - Jinwei, Huang; Xinfeng, Ge; Dongdong, Chu; Jing, Zhang; Bing, Xu; Fei, Gao; yuan, Zheng (Frontiers in Energy Research, 2022)
The position of the nozzle in the jet mechanism of the impulse turbine may cause an eccentric jet due to size processing and installation deviations. To study the effect of jet needle eccentricity on the jet, this article first analyzes the jet characteristics of the jet mechanism with different openings (20%, 40%, 60%, 80%, 100%) under 4.8% eccentricity, verify the reliability of the research method in this paper. Then the focus is on the jet characteristics of the jet mechanism at different eccentricities (0%, 1%, 2.1%, 4.8%, 8%, 14%) at 40% opening. The results show that as the eccentricity of the nozzle increases, the jet appears to be asymmetrical, and the shape of the jet at the inlet section of the runner gradually changes and becomes an irregular shape; The eccentricity of the water jet increases with the increase of the eccentricity of the needle; the efficiency of the injection mechanism gradually decreases, and the energy loss gradually increases. Before the eccentricity of 4.8%, the efficiency decreases more slowly, and after the eccentricity of 4.8%, the rate of efficiency decrease is accelerated.